TAFSIR AYAT CAHAYA DALAM MISYKĀT AL-ANWĀR DAN ORIENTASI PENDIDIKAN POTENSI DIRI - Salahuddin, Salahuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
The term ‘light’ in Sufism has become a favourite terminology in different cases. It has been one of central themes in the work of ‘sufi’. Al-Ghazālī proved his excellence when he interpreted the verses on light. The terms in those verses are interpreted as inner strengths of human such as senses, rationale, imagination, thinking, and intuition. These are lights by which the Almighty God leads human beings to get the fundamental light. This can, of course, be achieved by maximising human potentials through education.